2019
DOI: 10.29145/2019/jqm/030104
|View full text |Cite
|
Sign up to set email alerts
|

Corruption, Political Instability and Sustainable Development: The Interlinkages

Abstract: The study empirically probed the interdependence among corruption, political instability and sustainable development for a panel of 28 developing economies and disaggregated sample of lower-middle and upper-middle income economies for the time period 2000-2014. The three stage least square (3SLS) estimation revealed that corruption negatively affects sustainable development and political instability. The political instability impedes sustainable development and corruption. The sustainable development reduces p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Political instability harms economic growth, and some economists found that an unstable political situation harms economic activities in the nations, distracting local and foreign investors from investing in unstable economical environment. Moreover, a politically unstable environment increases inflation and unemployment, resulting in a decrease in economic growth (Khan & Farooq, 2019;Uddin, Ali, & Masih, 2017). Darby et al (2004) argued that unstable political situations minimize the likelihood of re-election, decreasing public investment and subsequently there occurs lower economic growth.…”
Section: Results Of Model 1 (Economic Growth)mentioning
confidence: 99%
“…Political instability harms economic growth, and some economists found that an unstable political situation harms economic activities in the nations, distracting local and foreign investors from investing in unstable economical environment. Moreover, a politically unstable environment increases inflation and unemployment, resulting in a decrease in economic growth (Khan & Farooq, 2019;Uddin, Ali, & Masih, 2017). Darby et al (2004) argued that unstable political situations minimize the likelihood of re-election, decreasing public investment and subsequently there occurs lower economic growth.…”
Section: Results Of Model 1 (Economic Growth)mentioning
confidence: 99%
“…Links between political stability and migration have also been highlighted, suggesting that politically stable regions tend to attract more migration, particularly from nations experiencing less stability [83,84]. Likewise, correlations have been identified between political stability and reduced corruption, implying that greater stability might coincide with lower levels of corruption [85,86]. Given that migrant population sizes and corruption are associated with factors shaping attitudes towards immigration, it's reasonable to anticipate a connection between political stability and attitudes towards immigrants.…”
Section: Indexes Behaviours and Attitudesmentioning
confidence: 99%
“…Corruption in developing countries is often carried out by diverting and exchanging government programme aid funds, which results in increasingly wasteful government spending. Unstable governance in developing countries causes vulnerability to property rights in their assets-are still unproductive and unable to pay for protection, which drives corruption (Khan, 2006;Khan & Farooq, 2019). This phenomenon has significantly influenced the decisions of many donor countries to provide assistance focusing on strengthening good governance difficulties.…”
Section: Introductionmentioning
confidence: 99%